(untitled) (Journal of actual problems of jurisprudence, 2018)
This article is sanctified to international cooperation in the countries of central Asia. In a publication the international are examined collaboration to water politics, transfrontal waters and ways are a decision. Key words: Water safety, transfrontal waters, water resources, convention, international state collaboration.